Stimulation of soluble guanylate cyclase improves donor organ function in rat heart transplantation - Benke, Kálmán; Németh, Balázs Tamás; Sayour, Alex Ali; Stark, Klára Aliz; Oláh, Attila; Ruppert, Mihály; Szabó, Gábor; Korkmaz-İçöz, Sevil; Horváth, Eszter Mária; Benkő, Rita; Hartyánszky, István; Szabolcs, Zoltán; et al. (Scientific reports, 2020)
Heart transplantation remains the definitive therapy of end-stage heart failure. Ischemia-reperfusion injury occurring during transplantation is a primary determinant of long-term outcome of heart transplantation and primary graft insufficiency. Modification of the nitric oxide/soluble guanylate cyclase/cyclic guanosine monophosphate signaling pathway appears to be one of the most promising among the pharmacological interventional options. We aimed at characterizing the cardio-protective effects of the soluble guanylate cyclase stimulator riociguat in a rat model of heterotopic heart transplantation. Donor Lewis rats were treated orally with either riociguat or placebo for two days (n = 9) in each transplanted group and (n = 7) in donor groups. Following explantation, hearts were heterotopically transplanted. After one hour reperfusion, left ventricular pressure-volume relations and coronary blood flow were recorded. Molecular biological measurements and histological examination were also completed. Left ventricular contractility (systolic pressure: 117 ± 13 vs. 48 ± 5 mmHg, p < 0.001; dP/dtmax: 2963 ± 221 vs. 1653 ± 159 mmHg/s, p < 0.001), active relaxation (dP/dtmin: −2014 ± 305 vs. −1063 ± 177 mmHg/s, p = 0.02; all at 120 µl of left ventricular volume), and alteration of coronary blood flow standardized to heart weight (2.55 ± 0.32 vs. 1.67 ± 0.22 ml/min/g, p = 0.03) were markedly increased following preconditioning with riociguat. Myocardial apoptosis markers were also significantly reduced in the riociguat pretreated group as well as the antioxidant markers were elevated. Pharmacological preconditioning with riociguat decreases ischemia-reperfusion injury and improves donor organ function in our animal model of heart transplantation. Therefore, riociguat might be a potential cardioprotective agent.
Gesehen am 08.10.2020